PENDIDIKAN ISLAM DALAM SISTEM PENDIDIKAN NASIONAL - Syafri Rizka Martabe Nasution (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2017)
Regarding religious education itself (Islam) basically quite enliven the Indonesian people, especially when viewed from a historical dimension, before the Dutch colonial government introduced Western education system is secular, it is known that the boarding school is the only formal education institutions in Indonesia, and it lasted for centuries. That's why the trip and the subsequent development of religious education can not be separated from the life of the Indonesian nation is predominantly Muslim, although in its operations always have ups and downs with all its dynamics. But it is clear the religious education or compulsory basic subjects of education that taught from elementary schools to the universities.